Kuliah Kerja Nyata (KKN) Gerakan Mahasiswa Peduli Stunting dengan Sosialisasi dan Pemberian Makanan Tambahan (PMT) Di Desa Paseh Kidul, Kecamatan Paseh, Kabupaten Sumedang: Pengabdian - Nizar Husni Halim; Tasya Augustiya; Dyah Safitri; Naiyla Septiani; Ghina Shafa Kamila; Izudin Al Mukhtar; Lintang Khaerunisa; Mila Kamelia Matmi; Nazwa Salsabila Nuryadin; Novia Fitriani; Rizki Abd.Rahman (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Stunting remains a serious health problem in Indonesia, particularly in rural areas such as Paseh Kidul Village, Paseh District. Lack of education about nutrition and proper parenting practices are key factors contributing to this situation. A Community Service (PKM) activity by students from the Muhammadiyah University of Bandung (UMB) Community Service Program (KKN) aims to increase public understanding of stunting prevention through an educational and participatory approach. The methods used in this activity included nutrition counseling through a seminar titled